The Substantive Urban Design Considerations: Priorities for Creating Successful Places - Konisranukul, Wanarat (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Although urban design, as opposed to urban design theories, is an ancient profession, that has shaped towns and cities over the centuries in many different cultures and continents, the agenda of urban design is new and different relative to other more established theories of late-twentieth-century town planning [1]. Whilst urban design theory as well as its practice still faces a number of challenges, in recent years many urban designers and planners seemingly agree that there is no single traditional urban design approach which could offer an absolute answer to successful urban design. Indeed, ‘successful urban design’ should not be employed as a fixed theoretical model but as the principles that underlie those successes, have value in empirical settings, and draw its intellectual roots from the past. In light of this concern, this paper is devoted to a discussion of the principles underlining successful urban design. Based on a review of both academic and professional works, five main substantive urban design considerations are proposed in this paper. These include physical function, visual perception, urban environment, heritage conservation, and social demand and development. Through the discussion, this paper shows that these substantive considerations play their important roles in urban design and help to generate successful urban design.